(untitled) (RIVISTA ITALIANA DI PALEONTOLOGIA E STRATIGRAFIA, 1990)
In the Upper Burdigalian-Lower Langhian sediments of the Venetian molassic basin two volcaniclastic layers are clearly recognizable, respectively within the Globigerinoides trilobus and Praeorbulina glomerosa zones of Bizon & Bizon (1972). The chemical composition of well-preserved glass shards, tested by electron microprobe, reveals rhyolitic composition and provides information about contemporaneous acidic explosive volcanism. Due to the probably depositional mechanism (fallout), the location of the effusive centres remains unknown. Although many ash layers are quite well-known in the same stratigraphic interval throughout the Apennine chain, a tentative correlation still seems very difficult, due to different methods of analysis and dating criteria.